The Effect of Price Perceptions on Purchase Decisions for Lion Air Aircraft Tickets at Sultan Hasanudin Airport, Makassar - Hodi Hodi; Muh Isna Abdi Negara (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Lion Air airline implements a Low Cost Carrier policy for economy class or with a minimum standard of service. It is hoped that the Low Cost Carrier policy will have a positive effect on ticket purchasing decisions, because there is a perception in the community, especially users of airport services, that low prices are often identified with low service quality below standard, while people expect low prices but quality service. Conditions like this can certainly affect the decision to buy a ticket. The purpose of this study is to determine the effect of price perceptions on purchasing decisions for Lion Air airplane tickets at Sultan Hasanuddin Airport, Makassar. This research uses a quantitative approach. The population in this study are Lion Air airline service users and the sampling technique in this study uses a probability sampling technique. Data collection techniques in this study used questionnaires with a total sample of 100 respondents. Processing data in research using the SPSS 21 software program. The analytical methods used are validity test, reliability test, simple linear regression, t test and coefficient of determination. The results of the t test on the price perception variable t-count is 11.410 and t-table is 0.195 so that it shows t-count t-table, so that H0 is rejected and Ha is accepted meaning that there is an influence of price perception (X) on purchasing decisions (Y) airplane tickets Lion Air at Sultan Hasanudin Airport Makassar. And the results of the coefficient of determination on the price perception variable is 57.1%, while the remaining 42.9% is explained by other variables outside this study. The results obtained in this study, namely the influence of price perceptions (X) on purchasing decisions (Y) for Lion Air flight tickets at Sultan Hasanudin Airport, Makassar, are known to be moderate correlation levels.